Effect of Different Liners on Fracture Resistance of Premolars Restored with Conventional and Short Fiber‐Reinforced Composite Resins. Issue 1 (11th January 2018) - Shafiei, Fereshteh; Doozandeh, Maryam; Ghaffaripour, Dordaneh
Abstract: Purpose: To see whether applying four different liners under short fiber‐reinforced composite (SFRC), everX Posterior, compared to conventional composite resin, Z250, affected their strengthening property in premolar MOD cavities. Materials and Methods: Mesio‐occluso‐distal (MOD) cavities were prepared in 120 sound maxillary premolars divided into 10 groups (n = 12) in terms of two composite resin types and 4 liners or no liner. For each composite resin, in 5 groups no liner, resin‐modified glass ionomer (RMGI), conventional flowable composite (COFL), self‐adhesive flowable composite resin (SAFL), and self‐adhesive resin cement (SARC) were applied prior to restoring incrementally. After water storage and thermocycling, static fracture resistance was tested. Data (in Newtons) were analyzed using two‐way ANOVA (α = 0.05). Results: Fracture resistance was significantly affected by composite resin type ( p = 0.02), but not by the liner ( p > 0.05). The interaction of the two factors was not statistically significant ( p > 0.05). SFRC exhibited higher fracture strength (1470 ± 200 N) compared to conventional composite resin (1350 ± 290), irrespective of the application of liners. Application of SARC and SAFL liners led to a higher number of restorable fractures for both composite resins. Conclusions: The four liners can be used without interfering with the higher efficacy of SFRC, compared to conventional composite resins, to improve the fracture strength of premolar MOD cavities.